2009
DOI: 10.5194/angeo-27-3725-2009
|View full text |Cite
|
Sign up to set email alerts
|

THEMIS observations of compressional pulsations in the dawn-side magnetosphere: a case study

Abstract: Abstract. We present THEMIS-A low-and high-energy plasma, magnetic field, and energetic particle observations of long period (11-36 min) irregular compressional pulsations in the dawnside magnetosphere from 08:00 to 12:24 UT on 7 November 2007. We demonstrate that the pulsations maintain thermal and magnetic pressure balance, then employ finite gyroradius techniques to determine wave properties from the gyrophase distributions of 5-10 keV ions. The waves generally move sunward at velocities ∼10 km s −1 with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
40
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 51 publications
14
40
3
Order By: Relevance
“…[18] We repeated the analyses of Korotova et al [2009] for the waves presented in this study and (in general) obtained similar results. By timing particle flux enhancements seen by duskward and dawnward looking sensors, we determine when flux enhancements reach locations 1 Rgyro (gyroradius) antisunward and sunward from the spacecraft and therefore the sunward component of the injection velocity, V = 2 Rgyro/ Figure 6.…”
Section: Wave Characteristicsmentioning
confidence: 61%
See 2 more Smart Citations
“…[18] We repeated the analyses of Korotova et al [2009] for the waves presented in this study and (in general) obtained similar results. By timing particle flux enhancements seen by duskward and dawnward looking sensors, we determine when flux enhancements reach locations 1 Rgyro (gyroradius) antisunward and sunward from the spacecraft and therefore the sunward component of the injection velocity, V = 2 Rgyro/ Figure 6.…”
Section: Wave Characteristicsmentioning
confidence: 61%
“…There are several ways to calculate their velocity. Korotova et al [2009] described how the characteristics of compressional pulsations can be determined from magnetic field and gyrophase observations. From top to bottom, Figure 5 presents THEMIS D ESA 7-12 keV ion gyrophase distributions integrated over 45°-135°, ion pitch angle distributions, the FGM magnetic field, and ESA ion number density moment from 1740 to 1845 UT.…”
Section: Wave Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, overall enhancements or decreases in wave energy ought to be associated with significant changes in the ion population, as would occur during a substorm injection or the recovery phase of a geomagnetic storm [e.g., Yang et al , 2010]. In the first panel in Figure 10, we show an ion energy flux spectrogram generated by the ESA and SST instruments on THD that includes energy ranges typically considered for drift bounce resonance [e.g., Korotova et al , 2009]. We find that there is a general decrease in the ion energy flux with time, with one peak occurring at ∼4 keV.…”
Section: Ulf Wave Modes That Are Inconsistent With Observationsmentioning
confidence: 99%
“…Toroidal pulsations have been attributed to a wide variety of mechanisms, including field line resonances triggered by abrupt changes and sudden impulses in the solar wind dynamic pressure (e.g., Zhang et al, 2010;Sarris et al, 2010), the Kelvin-Helmholtz instability (KHI) at the magnetopause (e.g., Pu and Kivelson, 1983;Fujita et al, 1996), and bursty reconnection and the generation of flux transfer events on the magnetopause (Gillis et al, 1987). Poloidal pulsations have also been attributed to a number of mechanisms, most notably drift-bounce resonances, ballooning modes, and drift mirror mode instabilities (Hasegawa, 1969;Lanzerotti et al, 1969;Hughes et al, 1979;Engebretson et al, 1992;Korotova et al, 2009;Liu et al, 2013). Arthur and McPherron (1981) presented a statistical study of 215 magnetic pulsation events identified on the basis of waveform and period as Pc 4 (45 to 150 s period) observed at synchronous orbit by ATS 6.…”
Section: Introductionmentioning
confidence: 99%